Pengaruh Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR) Terhadap Return on Equity (ROE) Pada PT. Bank Syariah Mandiri - Karmila Karmila (Journal Of Institution And Sharia Finance, 2021)
This thesis discusses the effect of Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR) on Return on Equity (ROE) at PT. Mandiri Syariah Bank. The main problem in this study is that banking as a business entity engaged in finance or finance really needs the trust of its customers to support and expedite the activities it undertakes. One of the ratios to measure banking performance is profitability or Return on Equity (ROE). The variables that affect the profitability (Return on Equity) of a bank are the Capital Adequacy Ratio (CAR) and the Financing to Deposit Ratio (FDR). Data were processed and analyzed using multiple linear regression using SPSS 22 for windows. The results of this study indicate that the Financing to Deposit Ratio has an effect of 42.9% on Return On equity, the Capital Adequacy Ratio has an effect of 19.6% on Return on Equity, and the Financing to Deposit Ratio and Capital Adequacy Ratio together have an effect of 62.5%. on Return on Equity.